Implementation of Total Quality Management (TQM) in Vocational High Schools (Analytical Study at SMK Karya Nugraha Boyolali Regency) - Ngatiman Ngatiman; Ki Supriyoko; A. Mufrod Teguh Mulyo (Journal Research of Social Science, Economics, and Management, 2022)
This study aims to describe: (1) the implementation of TQM in SMK Karya Nugraha Boyolali Regency; (3) supporting and inhibiting factors in the implementation of TQM at SMK Karya Nugraha Boyolali Regency. This research is a descriptive study using a qualitative approach. Data collection techniques used are interviews, observations, questionnaires and document studies. Furthermore, the collected data were analyzed using interactive model qualitative data analysis techniques. The results of this study indicate that: (1) Implementation of Total Quality Management (TQM) at SMK Karya Nugraha Boyolali Regency is indicated by the strategic plan, quality policy, upside-down organization, participatory and entrepreneurial leadership models, systems and procedures QMS ISO 9001:2015, conducting a self-assessment that has been running in accordance with quality guidelines and applicable legislation, supported by team work that has entered the hard work stage, in the last 3 years SMK Karya Nugraha Boyolali Regency has finally succeeded in realizing customer satisfaction, respect towards everyone, management based on facts and making continuous improvement.